Lingual Foramen of the Mandible on Cone-Beam Computed Tomography Scans: A Study of Anatomical Variations in an Iranian Population - Mahkameh Moshfeghi; Shiva Gandomi; Hamid Mansouri; Negin Yadshoghi (Tehran University of Medical Sciences, 2021)
Objectives: Lingual foramen (LF) is an important landmark of the mandible, which should be considered in presurgical assessment. The purpose of this study was to assess the anatomical variations of the LF using cone-beam computed tomography (CBCT). Materials and Methods: The study was conducted on 200 CBCT scans of Iranian adults. The lingual foramina (LFs) were classified into two groups by their location in the mandible namely the medial LFs (MLFs) and the lateral LFs (LLFs). The frequency of both the MLFs and the LLFs and their distance from the inferior border of the mandible were evaluated. Additionally, the diameter of the MLFs and the location of the LLFs were assessed. Data were analyzed separately for males and females. Results: All 200 participants had at least one LF. Totally, 257 LFs were detected on 200 CBCT scans, including 223 MLFs (86.6%) and 34 LLFs (13.3%). The LLF was detected in 23 patients (11.5%). The prevalence of the LLF was higher in males and in the second premolar region. The diameter of the MLFs was less than 1mm in 81% of the cases, and males had a larger MLF. Conclusion: There was a significant variability in the anatomy and location of the mandibular LF in Iranian adults. CBCT is recommended for preoperative imaging to determine the exact location and size of the LFs in the mandible to prevent possible surgical complications.